2014
DOI: 10.1021/tx500284g
|View full text |Cite
|
Sign up to set email alerts
|

Absolute Quantitation of NAPQI-Modified Rat Serum Albumin by LC–MS/MS: Monitoring Acetaminophen Covalent Binding in Vivo

Abstract: Acetaminophen is known to cause hepatoxicity via the formation of a reactive metabolite, N-acetyl p-benzoquinone imine (NAPQI), as a result of covalent binding to liver proteins. Serum albumin (SA) is known to be covalently modified by NAPQI and is present at high concentrations in the bloodstream and is therefore a potential biomarker to assess the levels of protein modification by NAPQI. A newly developed method for the absolute quantitation of serum albumin containing NAPQI covalently bound to its active si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 28 publications
0
32
0
Order By: Relevance
“…Ultra‐pure water was prepared from a Millipore Synergy UV system (Billerica, MA, USA). Iodo‐APAP ( N ‐(4‐hydroxyphenyl)‐2‐iodoacetamide) and d 4 ‐iodo‐APAP ( N ‐(4‐hydroxy[2,3,5,6‐d 4 ]phenyl)‐2‐iodoacetamide) were synthesized in‐house for chemical labeling of HSA and standard peptide to produce surrogate standard and internal standard (IS, see Figure B).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Ultra‐pure water was prepared from a Millipore Synergy UV system (Billerica, MA, USA). Iodo‐APAP ( N ‐(4‐hydroxyphenyl)‐2‐iodoacetamide) and d 4 ‐iodo‐APAP ( N ‐(4‐hydroxy[2,3,5,6‐d 4 ]phenyl)‐2‐iodoacetamide) were synthesized in‐house for chemical labeling of HSA and standard peptide to produce surrogate standard and internal standard (IS, see Figure B).…”
Section: Methodsmentioning
confidence: 99%
“…(N-(4-hydroxy[2,3,5,6-d 4 ]phenyl)-2-iodoacetamide) were synthesized in-house 30 for chemical labeling of HSA and standard peptide to produce surrogate standard and internal standard (IS, see Figure 1B).…”
Section: Iodo-apap (N-(4-hydroxyphenyl)-2-iodoacetamide) and D 4 -Iodmentioning
confidence: 99%
See 2 more Smart Citations
“…An alternative approach employed pepsin to digest NAPQI-Alb adducts in the mouse and also showed that the Cys34 was a major site of adduct formation. 117 …”
Section: Adduct Formation With Therapeutic Drugsmentioning
confidence: 99%